Correlates of self-reported distress in end-stage kidney dialysis patients using the distress thermometer score - Suree Yoowannakul; Surachet Vongsanim; Kamonwan Tangvoraphonkchai; Andrew Davenport (Renal Replacement Therapy)
Abstract Introduction Haemodialysis patients self-report increased levels of anxiety and depression. We wished to determine the prevalence of distress in a multi-ethnic dialysis population and patient factors associated with distress. Methods We reviewed self-reported distress thermometer (DT) scores from 971 haemodialysis patients with corresponding laboratory investigations, bioimpedance body composition and hand grip strength (HGS). Results The median age was 66.0 (55–75) years, 62.9% were male, 46.5% were of white ethnicity and 45.4% were diabetic. The results showed that 57.4% were classified as having no/minimal, 34% moderate, and 8.7% severe distress. Frailty increased from 31.5% to 47.9% and 56%, in the none/minimal, mild to moderate and severe distress groups (χ 2 17.6, p = 0.001), as did smoking (12.9% versus 16.7% versus 25%, χ 2 12.5, p = 0.001), and more patients reporting severe distress had suffered a previous myocardial infarction (MI) (17.4% versus 16.7% versus 27.4%, χ 2 7.1, p = 0.029). Haemoglobin decreased (109.6 ± 14.6 versus 107.6 ± 14.2 versus 103.5 ± 14.4 g/L, p < 0.001) as did HGS (18.9 (12.8–26.5) versus 17.1 (11.8–23.9) versus 15.4 (11.1–22.6) kg, p < 0.05). On ordinal multivariable analysis, increasing distress was associated with smoking (β 0.55, 95% confidence interval (CI) (0.17–0.92), p = 0.004), previous MI (β 0.47 (0.09–0.83), p = 0.015), serum calcium (β 1.11, (0.3–1.9), p = 0.007), lower age (β  −0.016, (−0.03 to −0.005), p = 0.003), haemoglobin (β  −0.014 (−0.02 to −0.004), p = 0.008) and HGS (β  −0.12 (−0.04 to −0.005), p = 0.013). Conclusion Younger age, higher calcium, lower haemoglobin and muscle strength, previous MI and smoking were associated with increasing levels of distress in this multi-ethnic dialysis population. Thus, both psychological and physical treatments are required to reduce stress levels for haemodialysis patients.